BIOACTIVE COMPOUNDS PROFILING IN Rumex vesicarius AND Terminalia catappa PLANTS USING GC-MS - SURYAVANSHI, ANANDIKA; SAXENA, A. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Medicinal plants constitute an innumerable number of valuable therapeutic metabolites. Their easy availability and lesser side effects, make them a suitable choice for bioactive compounds against various infectious diseases. This study highlights the phytochemical profiles of Terminalia catappa extract and Rumex vesicarius whole plant extract. Extracts of the plant prepared using soxhlet and preliminary phytochemical analysis done following standard chemical methods. The identification of the phytochemical was further done using FTIR and GC-MS techniques. The results indicate the presence of a wide range of phytochemical constituents in ethanolic, methanolic, aqueous, hexane, and acetone extracts of Terminalia catappa and Rumex vesicarius plant.